Analysis of Factors Related to Patients Satisfaction - Dewi Rahayu; Dwi Yuli Maritasari; Astiana Al’dila (GLOBAL HEALTH SCIENCE GROUP, 2021)
The effort of a hospital to survive and develop is to improve services to patients. Hospitals can do various ways to increase patient visits, so the hospital must be able to display and provide good health services, so that the impact that arises will make patients come back to take advantage of the hospital's services. RSU Islam has the lowest percentage value of customer satisfaction compared to other public private hospitals located in Metro City. The purpose of this study was to determine the factors related to outpatient satisfaction at the Metro Islamic Hospital in 2020. This study used a cross-sectional study design. The study population was the target population in this study, the average monthly outpatient who received services at the Islamic Metro Hospital was 1,098, while the sample chosen was 98 people. Data collection was done by employing a questionnaire that has been tested for validity and reliability and filled directly by the respondents, while data analysis was done by using logistic regression. The results showed that there was a relationship between perceptions of reliability (p value 0.000), responsiveness (p value 0.045), assurance (p value 0.048), empathy (p value 0.000), and physical evidence (p value 0.000) with outpatient satisfaction at Metro Islamic Hospital in 2020. Reliability is the most dominant factor related to outpatient satisfaction at Metro Islamic Hospital in 2020, where has the highest OR value of 7.218.